Conexões epistemológicas entre Charles Darwin e alguns autores: uma investigação filosófica e evolutiva do pensamento científico - Silva, Phelipe Martins da (2014)
The epistemology is an important branch of philosophy responsible for studying the relationships of nature, origin and validation of knowledge. It is through this philosophy of science that we can trace connections between the illustrious English naturalist Charles Darwin and some authors in chronological order, where we begin to establish bonds from ancient Greece until the present times, contemplating the main purpose of this work. We used the method of the literature review and proceeded with bibliographic survey, where we collected data from various sources, including books, articles, online databases, journals, among others, with the purpose of giving substation to the referencial theoretical. This latter was divided into a brief historic of the evolutionary thought before and after Darwin, to provide the reader with the ability to differentiate and monitor the development of human understanding on the subject over time. We observed that the idea of biological evolution was already inculcated in people since classic antiquity, however, they lacked the ability to provide solid arguments based on consistent scientific criteria, which only became possible with the publication of the theory of natural selection proposed by Charles Darwin in 1859. Therefore, we believe that the history and philosophy of science are fundamental in understanding the scientific thought, contributing and enriching the knowledge constructed by man.